FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERSALINAN PRETERM DI RSUP DR. M. DJAMIL PADANG TAHUN 2013 - Mutia Felina, Mutia; Yeltra Armi, Yeltra (LPPM Universitas Prima Nusantara Bukittinggi, 2013)
Most perinatal deaths occurred in developing countries, including Indonesia. One of the major contributing factors to the high AKB in Indonesia is preterm delivery by 29%. The incidence of preterm birth at RSUP DR. M. Padang djamil 3 years a significant increase. In 2010 with a percentage of 14.03%, increasing to 15.74% in 2011, then increased in 2012 to 15.89%. The purpose of this study was to determine the factors associated with the incidence of preterm birth at RSUP DR. M. Djamil Padang in 2012. This type of research is analytic survey with case control design. The research was conducted on 14 to 25 October 2013. The study population was all women giving birth in the department of RSUP DR. M. Djamil the month of January to December 2012. Samples totaling 73 sample cases and 73 control samples were taken by simple random sampling method. Types of research data is secondary data. Data is manually processed and analyzed through univariate and bivariate analysis with the Chi-Square test statistic. The results showed that 50% of mothers in the maternity department of RSUP DR. M. Padang djamil a preterm delivery. 30.14% by age-risk maternity. 33.56% with parity-risk maternity. Maternity 36.99% with hypertension. From the bivariate analysis, obtained Ï‡ 2 = 14.346 h for relationship age, parity relations for 31.454, 18.367 to the relationship with the incidence of hypertension persalian preterm, with Ï‡ 2 t = 6.63, bivariate analysis of all the obtained Ï‡2 h â‰¥ Ï‡2t which means HO rejected. Based on the obtained results of analysis of the relationship of age, parity and hypertension of membranes with the incidence of preterm birth. Expected to health care through the department of RSUP DR. M. Djamil Padang in order to improve the quality of ANC services, especially in dealing with at-risk pregnancies occurrence of preterm birth.